Dramas of the Commons in Brazil - Sawyer, Donald (Sustainability in Debate, 2013)
This article examines experiences with commons, both tragic and successful, in local communities in Brazil. The problem for collectors is not limited to land, but also includes their access to natural resources outside their territories. Use rights could be established, regulating wild collection on land of third parties or government. Access to such commons should be limited to members of specific groups through private agreements regulated by official norms. Conclusions and recommendations for research and policy include, among others: 1) priority or communities under the greatest pressure, 2) land reform which provides for access to natural resources outside individual lots, 3) regulation of sustainable use in various kinds of protected and reserved areas, 4) inclusion of families with off-farm activity and multiple residence. Sustainable productive landscapes are the only way to achieve the scale necessary to maintain ecosystem functions of aquatic resources, biodiversity and carbon (“ABC”).